À l’école des temps faibles. Quelques enjeux didactiques d’une éducation en mineur - Thibaut Bouchet-Gimenez (Recherches en Éducation)
Can non-regular forms of transmission emerging clandestinely in the classroom be of interest to didactic research if we postulate that this latter is genetically linked to the strong framing of teaching-learning situations? To answer this question, this article tries to show how the appropriate loosening of the forced times of the classical school form secretes temporalities that can maintain the continuity of the school experience in its epistemic valence. The school education is seized here in its minor modality which, with regard to the asserted mastery of the whole of the conditions of the diffusion of the knowledge typical of an education in major, gives to see a didactic process characterized by its precariousness and its fallibility. This text tries to approach theoretically, to circumscribe ethically and to illustrate in the practice these didactic weak times by the description of “facilitation” as a gesture of minor study and by the presentation of the “moment game” as a micro-situation allowing the passage towards an epistemic relation to the world.